A death retold : Jesica Santillan, the bungled transplant, and paradoxes of medical citizenship - Wailoo, Keith; Livingston, Julie; Guarnaccia, Peter Joseph (Studies in social medicine., 2006)
In February 2003, an undocumented immigrant teenager from Mexico lay dying in a prominent American hospital due to a stunning medical oversight - she had received a heart-lung transplantation of the wrong blood type. In the following weeks, Jesica Santillan's tragedy became a portal into the complexities of American medicine, prompting contentious debate about new patterns and old problems in immigration, the hidden epidemic of medical error, the lines separating transplant 'haves' from 'have-nots', the right to sue, and the challenges posed by 'foreigners' crossing borders for medical care.